2021
DOI: 10.1186/s13014-021-01751-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of breast cancer cells using AS1411 aptamer-conjugated gold nanoparticles

Abstract: Background Gold nanoparticles (GNPs) have been used to sensitize cancer cells and enhance the absorbed dose delivered to such cells. Active targeting can provide specific effect and higher uptake of the GNPs in the tumor cells, while having small effect on healthy cells. The aim of this study was to assess the possible radiosensitiazation effect of GNPs conjugated with AS1411 aptamer (AS1411/GNPs) on cancer cells treated with 4 MeV electron beams. Materials and me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 61 publications
(82 reference statements)
0
14
0
Order By: Relevance
“… 3 However, since its first introduction, 4 various studies reported the anticancer effect of AS1411 in various types of cancers. 5 , 6 , 7 , 8 We used a modified type of this aptamer (AS1411) demonstrated by C’C’T‐AS1411 (IO101) and C’C’T‐AS1411‐TGG (IO101L) (see Figure 2 ). We evaluated the effect of stability and solubility in C’C’T‐AS1411‐TGG (IO101L) compared with C’C’T‐AS1411 (IO101).…”
Section: Methodsmentioning
confidence: 99%
“… 3 However, since its first introduction, 4 various studies reported the anticancer effect of AS1411 in various types of cancers. 5 , 6 , 7 , 8 We used a modified type of this aptamer (AS1411) demonstrated by C’C’T‐AS1411 (IO101) and C’C’T‐AS1411‐TGG (IO101L) (see Figure 2 ). We evaluated the effect of stability and solubility in C’C’T‐AS1411‐TGG (IO101L) compared with C’C’T‐AS1411 (IO101).…”
Section: Methodsmentioning
confidence: 99%
“…However, as evidenced previously, breast-cancer-cell-specific aptamer AS1411 can be conjugated with a PROTAC molecule (as inspired by antibody–drug conjugates) as a delivery means to selectively target cancer cells over normal cells [ 21 ]; this constitutes the third layer of precision targeting. One could use structurally modified AS1411 as an alternative [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ], because AS1411 was withdrawn from clinical trials [ 103 ]. The main reason for the withdrawal of AS1411 from clinical trials was its insufficient anti-cancer activity; meanwhile, its safety issue was found to be good [ 44 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…For example, As1411 is a guanine-rich DNA aptamer with high specificity and affinity to nucleolin receptors which are only overexpressed on the plasma membrane of cancer cells. The specific interaction between As1411 and nucleolin has been used to mediate the highly specific targeting of radiosensitizers to cancer cells [ 126 , 127 , 128 , 129 ]. As1411-conjugated gold nanoparticles [ 128 ], gold nanoclusters [ 126 ], or silver nanoparticles [ 127 , 129 ] have been proved to be capable of acting as efficient radiosensitizers for cancer targeting treatment.…”
Section: Affinity Ligands and Corresponding Applications In Radiotherapymentioning
confidence: 99%